Quantitative Analysis, Anti-Inflammatory and Analgesic Effects of Ethanol Leaf Extract and Fractions of Microsorium scolopendria (Burm. f.) Copel. in Mice - Umoh, Uwemedimo Francis; Ubengama, Ekikere Ezekiel; Ramos, Gina; Onyido, Victor Chubueze (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Microsorium scolopendria, a fern was studied for phytochemicals, anti-inflammatory, and analgesic effects to add credence to its various folkloric applications. Phytochemicals were analyzed quantitatively, anti-inflammatory experiment was carried out with egg albumin- induced paw oedema and xylene-induced ear oedema models while analgesic effects were studied using formalin-induced paw licking, acetic acid-induced writhing and hot plate-induced pain models. The results revealed the presence of alkaloids, flavonoids, saponins, tannins, terpenoids, and phenols with alkaloids (14.6 %w/w) as the most predominant phytoconstituent. In anti-inflammatory experiments, M. scolopendria extract reduced oedema caused by egg albumin and xylene in a dose related manner and comparable to standard agents. Also, in analgesic experiments, the extract reduced pain induced by formalin, acetic acid, and hot plate. These reductions were statistically (p?0.05) significant. Considering the fractions in all experiments, butanol and ethyl acetate fractions were prominent in anti-inflammatory effect while ethyl acetate fraction was at top in reduction of pain. This study supports the use of M. scolopendria in ethnomedicinal practice.